Wandering Son. Volume five - Shimura, Takako, 1973- (Fantagraphics Books, 2013)
Nitori Suichi--a boy who identifies as a girl--and Tatakutsuki Yoshino--a girl who identifies as a boy--continue to navigate sexual identity and preteen relationship issues as they enter their first year of junior high.